Evaluation of p53, HoxD10, and E-Cadherin Status in Breast Cancer and Correlation with Histological Grade and Other Prognostic Factors. (30th January 2014) - Sekar, Preethi; Bharti, Jyotsna Naresh; Nigam, Jitendra Singh; Sharma, Ankit; Soni, Priyanka Bhatia
Abstract : Background . Study of tumor molecular characteristics is necessary to understand both the risk of breast cancer recurrence and the response to therapy. Aims . To evaluate p53, HoxD10, and E-cadherin status in breast cancer and to correlate with histological grade and other prognostic factors. Material and Methods . The study was conducted in 60 cases of invasive ductal carcinoma NOS with 20 cases belonging to each grade and evaluation of p53 was done by IHC and that of HoxD10 and E Cadherin status by PCR and correlation was done with histological grade and other prognostic factors. Result . p53 expression was seen in 71.67% (43/60) of the tumors. HoxD10 gene was downregulated in 46.67% (28/60) of the tumors. p53 overexpression and lower HoxD10 mRNA levels showed statistically significant association higher histological grade of the tumor (P < 0.05 ). CDH1 gene mutation was seen in 60% (15/25) of the tumors. No significant association was found between p53 expression, HoxD10 gene, CDH1 gene mutation, and other prognostic factors. Conclusion . p53 over expression and lower HoxD10 mRNA levels were found to be significantly associated with higher grade tumours. This suggests that p53 and HoxD10 gene play an important tumor suppressor role and the loss of which results in breast cancer progression.